Cross-cultural adaptation and psychometric properties of the Chinese version of the Orthorexia Nervosa Inventory - Sun, Xinzhang; Lu, Ying; Jian, Chengping; Zhang, Hanqing (Frontiers in Nutrition, 2025)
BackgroundOrthorexia nervosa refers to an unhealthy preoccupation with maintaining a perfect diet, which is marked by highly restrictive eating habits, rigid food rituals, and the avoidance of foods perceived as unhealthy or impure. In recent years, the Orthorexia Nervosa Inventory (ONI) has gained recognition as a promising tool for assessing orthorexia tendencies and behaviors, addressing the limitations of existing ON-specific measures. This study aimed to evaluate the psychometric properties of the Chinese version of the ONI.MethodsA total of 717 participants (Mage = 20.11 years, 78.66% female) completed the Orthorexia Nervosa Inventory (ONI) alongside the Chinese version of the Düsseldorf Orthorexia Scale (C-DOS). The ONI was translated into Chinese using the Brislin traditional translation model, following formal authorization from the original author. This translation process included literal translation, back translation, and cultural adaptation to ensure both linguistic and contextual fidelity. Item analysis was employed to assess item differentiation. Scale reliability was determined by measuring internal consistency. Furthermore, exploratory and confirmatory factor analyses were conducted to investigate and confirm the underlying factor structure and overall validity of the scale.ResultsThe Chinese version of the Orthorexia Nervosa Inventory (ONI) consists of 24 items across three dimensions. The overall Cronbach’s alpha coefficient for the scale was 0.956, indicating excellent internal consistency. The Cronbach’s alpha coefficients for the individual dimensions were 0.894, 0.933, and 0.848, respectively, demonstrating high reliability for each dimension. Additionally, McDonald’s ω was 0.957 for the entire scale, reflecting strong stability in internal consistency, with individual dimensions having McDonald’s ω coefficients of 0.895, 0.934, and 0.854. The Spearman-Brown split-half reliability coefficient was 0.931, and McDonald’s ω for the split-half reliability was also 0.931, indicating excellent consistency across the scale’s two halves. The test–retest reliability was 0.987, with a 95% confidence interval ranging from 0.978 to 0.993, suggesting excellent stability over time and strong consistency across different measurement points. All model fit indices fell within acceptable ranges, affirming the structural validity of the Chinese version. The results from both exploratory and confirmatory factor analyses further supported this conclusion.ConclusionThis study successfully translated and culturally adapted the ONI into Chinese, followed by a comprehensive evaluation of its psychometric properties. The findings demonstrate that the Chinese version of the ONI possesses strong reliability and validity. In the context of varying cultural backgrounds and dietary habits, this scale serves as a valid tool for assessing and screening the Chinese ON population.